(untitled) (Research, Society and Development, 2025)
Objective- To explore the point of view of residents in the communities of Porto Velho and neighboring communities on malaria testing, risks and related benefits. Methodology- Rapid and participatory appreciation of community needs through an ethnographic assessment to explore community beliefs/practices related to specific interventions related to the diagnosis and treatment of a given disease. Data collection took place through focus groups and individual face-to-face interviews (August 2022). Results- Participants were 21 women and 17 men, both adults and educated. All participants in the focus groups and 90% of the interviewees knew of malaria cases among family members and friends. Among the interviewees, the majority are adult men, employed/self-employed, while most of the participants in the groups are women, young people, employees or students. The findings revealed how previous endemics affected community perceptions of malaria testing. Exposure to malaria in social circles reinforced the belief of uncontrollable environmental risk. A spectrum of critical issues was revealed: widespread apathy and fear, increased awareness of malaria recurrence, perceptions of its urban sprawl, recognized importance of testing and treatment, and barriers to effective testing and treatment. Participants shared and critiqued thoughts on communities’ thinking about malaria testing. Conclusion- Concern with the environment-human health requires greater political engagement in the sociocultural context of malaria. Proposed recommendations include mass education and communication, action by community agents, availability of testing technicians, and increased testing sites.